Reliability and construct validity of the scale of knowledge, attitude and practice of medical doctors on smoking cessation guidelines - Mohd Shaiful Ehsan bin Shalihin (Kulliyah of Medicine, International Islamic University Malaysia, 2017)
Introduction: Islam forbids any forms of tobacco. Prevalence of active smokers in Malaysia is increasing despite the availability of stop-smoking clinics. Therefore, knowledge, attitude and practice of the healthcare professional on smoking cessation intervention needs to be assessed using validated assessment tool. Objective: This study aimed to develop and validate a questionnaire to assess the knowledge, attitude, and practice of medical doctors based on national smoking cessation guidelines and factors contributing to the score. Methods: The 26 items consists of a mixture of true/false choice questions and Likert scaling response based on the domain of 5A's (ask, assess, advice, assist, arrange) and 5R's (relevant, risks, rewards, roadblocks, repetitions) of the national stop-smoking guidelines. The questionnaires were distributed to 141 medical doctors. Reliability was determined using Cronbach's alpha for internal consistency while construct validity was assessed using factor analysis. Results: A high degree of internal consistency was observed for these 26 items (Cronbach's alpha = 0.824) and for practice subscale (Cronbach's alpha = 0.826). Subsequently, 3 items were removed due to poor inter-item correlation. Factor analysis extracted 7 meaningful components from this remaining 23 items, in which 3 components with least items were deleted due to overlapping subscale with other components, leaving 4 meaningful components, consist of (1st) practice of ask, advice and assess component and practice 5R's (total 10 items), (2nd) practice of assist and arrange component for those willing to quit (2 items), (3rd) knowledge (2 items) and (4th) attitude (3 items). These final 17 items still demonstrate high internal consistency with Cronbach's alpha of 0.832. Conclusion: This study indicates that this questionnaire is a reliable and valid tool to assess the knowledge, attitude, and practice on stop smoking guidelines